Mencari Manajemen Pendidikan Yang Tepat Untuk SMA di Jawa Timur - Made Pidarta (Universitas Negeri Malang, 2016)
This study on educational management is conducted in 1991 of which the respondents comprises 24 principals of SMAN and private ones. The instruments used is an interview schedule. The result shows that the strength of management is in the school climate, the methods to motivate students, and some extra curriculair activities. This management is to be called practical management as it affects the students directly in promoting their achievements.